Supporting Multilingual Students’ Mathematical Discourse Through Teacher Professional Development Grounded in Design-Based Research: A Conceptual Framework - Margarita Jiménez-Silva; Robin Martin; Rachel Restani; Suzanne Abdelrahim; Tony Albano (Education Sciences)
This conceptual paper presents a framework for supporting multilingual students’ mathematical discourse through teacher professional development grounded in design-based research (DBR). Drawing on sociocultural learning theory, the Integrated Language and Mathematics Project (ILMP) was co-developed with elementary educators to promote integrated instruction that simultaneously advances students’ mathematical understanding, language development, and cultural identity. The ILMP framework centers around three instructional pillars: attention to language, attention to mathematical thinking, and cultural responsiveness. Through collaborative inquiry cycles, educators engaged as learners, contributors, and designers of practice, iteratively enacting and reflecting on instructional strategies rooted in students’ linguistic and cultural assets. Teachers implemented discussion-rich mathematical tasks, supported by language scaffolds and culturally relevant contexts, to foster students’ mathematical reasoning and communication. This approach was particularly impactful for multilingual learners, whose language use and problem-solving strategies were both valued and elevated. This paper also discusses the opportunities and challenges of DBR and research–practice partnerships, including flexibility in implementation and navigating district-level priorities. Insights underscore the importance of practitioner agency, asset-based pedagogy, and the co-construction of professional learning. The ILMP framework offers a scalable, equity-oriented model for improving integrated language and mathematics instruction in diverse elementary classrooms and beyond.